Implementation Plan In Response To The Executive Board-Endorsed Recommendations From The IEO Evaluation Of The IMF's Financial Surveillance. - International Monetary Fund. Strategy, Policy, and Review Department (Washington, D.C. : International Monetary Fund, 2019)
The actions in this Management Implementation Plan aim at: -- Strengthening financial and macrofinancial analysis in Article IV consultations -- Refocusing FSAP country selection and scope -- Increasing traction of multilateral surveillance -- Enhancing the IMF's macrofinancial analysis toolkit -- Building financial skills and expertise at the Fund.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet